12 monkeys ein Terry-Gilliam-Film - Buckmaster, Paul 1946-2017 (Concorde Home Entertainment, 2007)
In a future world devastated by disease, a convict is sent back in time to gather information about the man-made virus that wiped out most of the human population on the planet. (IMDb). - Inspiration durch den Film "La jetée"
Original: USA 1995
Bonus-Material (circa 90 min): Deutscher Kinotrailer; The Making of "12 monkeys" oder "Der Hamster-Faktor"; Bio- und Filmografien der Hauptdarsteller und des Regisseurs; Produktionsnotizen; Trailer von Lara Craft: Tomb Rainer - Die Wiege des Lebens; colortitle (farbige UT für Hörgeschädigte)
"Inspiration durch den Film "La jetée, Buch: Chris Marker" (Rückseite der DVD-Hülle)
Bildformat 1.85:1 (16:9 anamorph)
Keywords: Twelve monkeys; Film; DVD-Video